Upaya Meningkatkan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Discovery Learning pada Peserta Didik Kelas IX.6 SMP Negeri 42 Palembang - Sri Oktaviana (Journal on Education, 2022)
The application of ordinary learning carried out in class IX.6 at SMP Negeri 42 Palembang has not used an effective learning model, the average value of student learning outcomes is 66 and learning completeness reaches 36.67% or there are 11 students out of 30 students who have finished studying. This is because students still feel they are not optimal and do not understand what the teacher is explaining so that learning outcomes are still low. class IX.6 SMP Negeri 42 Palembang with the number of students 30 people. This study aims to determine the increase in student learning outcomes in class IX.6 SMP Negeri 42 Palembang after the implementation of the Discovery Learning learning model so that learning Mathematics becomes more fun and raises the creativity of participants educate. This research was formulated, namely "Is the implementation of the Discovery Learning Learning Model able to improve the mathematics learning outcomes of class IX.6 students of SMP Negeri 42 Palembang?". This study uses two rounds of action research (classroom action research). Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The targets of this study were students of class IX.6 SMP Negeri 42 Palembang. From the results of the analysis, it was found that student learning outcomes had increased from pre-cycle (36.67%), cycle I (56.67%) and cycle II (86, 67%). The conclusion of this study is that the Discovery Learning learning model can have a positive effect on the learning outcomes of students at SMP Negeri 42 Palembang, and this learning model can be used as an alternative to learning Mathematics.